A rapid extraction method for glycogen from formalin-fixed liver. (15th March 2015) - Sullivan, Mitchell A.; Li, Shihan; Aroney, Samuel T.N.; Deng, Bin; Li, Cheng; Roura, Eugeni; Schulz, Benjamin L.; Harcourt, Brooke E.; Forbes, Josephine M.; Gilbert, Robert G.
Highlights: Diabetic and healthy mice have different glycogen structures. Applicable to humans? This develops a method for extracting glycogen from formalin-fixed liver. This allows for analysis of formalin-fixed healthy and diabetic human tissues. Formalin extraction method is much more rapid than cold-water techniques. Proteomics is also compatible with this formalin extraction technique. Abstract: Liver glycogen, a highly branched polymer, acts as our blood-glucose buffer. While past structural studies have extracted glycogen from fresh or frozen tissue using a cold-water, sucrose-gradient centrifugation technique, a method for the extraction of glycogen from formalin-fixed liver would allow the analysis of glycogen from human tissues that are routinely collected in pathology laboratories. In this study, both sucrose-gradient and formalin-fixed extraction techniques were carried out on piglet livers, with the yields, purities and size distributions (using size exclusion chromatography) compared. The formalin extraction technique, when combined with a protease treatment, resulted in higher yields (but lower purities) of glycogen with size distributions similar to the sucrose-gradient centrifugation technique. This formalin extraction procedure was also significantly faster, allowing glycogen extraction throughput to increase by an order of magnitude. Both extraction techniques were compatible with mass spectrometry proteomics, with analysis showing the two techniques were highly complementary.